Back to school after the pandemic: Adjustment of Spanish children and adolescents. - Orgilés, Mireia; Serrano-Ortiz, Marina; Espada, Jose Pedro; Morales, Alexandra (Anales de Psicología / Annals of Psychology, 2024)
Aiming to mitigate the COVID-19 spread, the government of Spain applied restrictive measures, like schools’ closure. Although the effects of the pandemic on children’s emotional well-being have been studied, there is a lack of studies examining school adjustment following the pandemic and the role that the infection has played in the adjustment process. The objective is to analyze the relationship between stressful events related to school experienced by children and their adjustment to school after the home confinement, including anxiety as a mediator variable. Participants were the parents of 219 Spanish children and adolescents aged 3 and 18 years who completed a survey about their children’s anxiety (Spanish Brief Child Version of the Spence Children’s Anxiety Scale), the stressful events experienced related to school (Stressful Events related to Pandemic Inventory), and the adjustment to school (Adjustment of Children after Pandemic School Closure Scale). Results showed that social distance was the most reported stressful event (87%). Having COVID-19 and experiencing bullying were directly related to a high level of anxiety. Children´s who decreased social contact and experienced bullying showed a worse adjustment to school. Anxiety was an indirect mediator of this relationship. Findings highlight the importance of supervising school adaptation and promoting strategies to prevent emotional problems when the youths are exposed to stressful situations.